The Impact of Food on Muslims Spiritual Development - Nazihah, Apap; Arifin, Bambang Samsul (UIN Sunan Gunung Djati Bandung, 2020)
Islam is a religion that regulates all aspects of human beings. Muslims in Indonesia generally focus on the discussion about fiqh ibadah, but less concern on many aspects of fiqh muamalah. If it is not understood correctly, doubtful (syubhat) goods and services leading to haram might be consumed by the muslims and influenced their spiritual development. This study aims to explain the impact of food consumption on the spiritual development in Islam. The finding of this study indicates the influence of food consumed by humans might affect psychological aspects, such as emotion. The consuming habits without considering halal and haram, or anything materialistic will lead to temporary satisfaction. Whatever is developed by such people, whether science, technology, creativity, and any innovation, will bring damage or danger to the survival of humans, society, and the natural surroundings.